The Mechanism of Alkali Metal Ion Sorption by Iron(III) Phosphate - S. Mustafa; A. Naeem; S.U. Nisa; S. Murtaza; M. Khalid (Adsorption Science & Technology)
Alkali metal ion exchange (Li + , Na + and K + ) on iron(III) phosphate (FePO 4 ) was studied potentiometrically as a function of temperature and metal ion concentration. The uptake behaviour of iron(III) phosphate was inferred from a comparison of the K + ions sorbed and the loss of H + ions from the exchanger. FT-IR spectroscopic studies and dissolution studies of FePO 4 confirmed the uptake mechanism of alkali metal cations as cation exchange. The potentiometric titration data were employed to evaluate the apparent dissociation constants of iron(III) phosphate which were found to depend on the temperature of the system. The corresponding thermodynamic parameters ΔH 0 and ΔS 0 were also evaluated.